Trances in Perspectives of Javanese and Muslim: An Anthropological Linguistic Study - Budiman, Arif; Wulandari, Ari; Khristianto, Khristianto (Indonesian Journal of EFL and Linguistics, 2023)
Possession is a serious health problem for Javanese and Muslims. This study aims to describe the perspective of Javanese and Muslims on a trance or a state of being possessed. This is qualitative research applying a linguistic anthropological approach. The subjects are the members of the Javanese and Muslim communities in Tulungagung. They are the individuals having experienced trance(s), their family, and the witnesses. Other important informants are the healers, shamans, and Islamic leaders (ustadz or kyai). Based on the analysis, it shows that trance for the Javanese is a disease inflicted by a certain spirit. It must be cured by a shaman with a series of rituals and offerings. For Muslims, it is a disturbance of the genie as the possessed disobeys God’s rules. Its healing is done through ruqyah by reciting particular verses from the Qur'an. The way Javanese treats a trance reflects their perspectives and thoughts as found in local wisdom: tamba teka lara lunga (the cure comes and the disease goes), meaning that every disease has its cure. For Muslims, a trance is simply an effect of the human relation to his God. A better quality in the relationship will result in a human’s better life. Conversely, a bad relationship to God will bring about a negative quality in human life. Trance is just one of them; it is believed to be evidence of the poor relationship a possessed has to God.